2006
DOI: 10.1111/j.1471-4159.2006.04339.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective role of bradykinin because of the attenuation of pro‐inflammatory cytokine release from activated microglia

Abstract: Bradykinin (BK) has been reported to be a mediator of brain damage in acute insults. Receptors for BK have been identified on microglia, the pathologic sensors of the brain. Here, we report that BK attenuated lipopolysaccharide (LPS)-induced release of tumor necrosis factor-alpha (TNF-a) and interleukin-1b from microglial cells, thus acting as an anti-inflammatory mediator in the brain. This effect was mimicked by raising intracellular cAMP or stimulating the prostanoid receptors EP2 and EP4, while it was abol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 77 publications
4
75
0
1
Order By: Relevance
“…Previously, PGE 2 was shown to block innate immune responses from microglia in vitro via EP2 and EP4 (16,17,35). Here, we found that EP2-and EP4-expressing spinal microglia had an amoeboid morphology that is characteristic for activated microglia.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previously, PGE 2 was shown to block innate immune responses from microglia in vitro via EP2 and EP4 (16,17,35). Here, we found that EP2-and EP4-expressing spinal microglia had an amoeboid morphology that is characteristic for activated microglia.…”
Section: Discussionsupporting
confidence: 52%
“…However, PGE 2 also has anti-inflammatory properties. It mediates bradykinininduced neuroprotection and blocks LPS-and ATP-induced cytokine synthesis in cultured microglia or in neuron-glia cocultures (16,17). The anti-inflammatory and neuroprotective effects of PGE 2 are suggested to be mediated via microglial EP2 and EP4 receptors.…”
mentioning
confidence: 99%
“…118 The potential role for these agents in managing neurological disorders that exhibit an inflammatory component has also been mooted, 119 although there is also some evidence to suggest that bradykinin may have antiinflammatory and neuroprotective effects in the CNS by modulating microglial function. 120 Bradykinin receptor antagonists have been shown to improve neurological outcome following TBI, 121 in part by attenuating the increase in ICP. 122 The tachykinins, which include substance P and neurokinin A, are released from nerves in the active form and produce their effects via tachykinin receptors.…”
Section: Kinin Antagonistsmentioning
confidence: 99%
“…The addition of BK to the microglia culture induced B1BKR expression, while B2BKR expression was up to 50% down regulated (Noda et al, 2003(Noda et al, , 2004. During inflammation, BK is neuroprotective by up-regulating expression rates of kinin receptor, which are responsible for reducing microglia-induced proinflammatory responses in the presence of lipopolysaccharide (LPS), leading to inhibition of TNF-α and IL-1β expression (Noda et al, 2007b). According to the author, BK prevents proinflammatory effect via B1BKR activation.…”
Section: Kinins In Microglia Cellsmentioning
confidence: 99%
“…In addition to neuroprotective roles of BK (Yasuyoshi et al, 2000;Noda et al, 2007b;Negraes et al, 2015), that kinins are able to induce neuroinflammatory responses (Passos et al, 2013). It has been shown that, in some neurodegenerative and pathological conditions, IL-1β and TNF-α secreted by infiltrating leukocytes promote up-regulation of B1BKR expression.…”
Section: Neuroprotection and Inflammatory Responsesmentioning
confidence: 99%